Magnetic reduced graphene oxide loaded hydrogels: highly versatile and efficient adsorbents for dyes and selective Cr(VI) ions removal - Halouane, Fatima; Oz, Yavuz; Meziane, Dalila; Barras, Alexandre; Juraszek, Jean; Singh, Santosh K.; Kurungot, Sreekumar; Shaw, Pankaj K.; Sanyal, Rana; Boukherroub, Rabah; Sanyal, Amitav; Szunerits, Sabine (Journal of Colloid and Interface Science, 2017)
The formation of composites of reduced graphene oxide (rGO) and magnetic nanoparticles (MP) has flourished in recent years as they combine the advantages of both nanomaterials. Most of these composite materials are prepared by in situ formation of MP onto rGO or by the post-adsorption onto rGO. We report here on a simple and highly controlled method for the fabrication of different magnetic 3D rGO-loaded hydrogels. Cellulose bound magnetic nanoparticles (MP@cellulose) were synthesized by chemical co-precipitation and loaded together with rGO into poly(ethylene glycol) dimethacrylate based hydrogels during their fabrication using photo-polymerization. The magnetic rGO-loaded hydrogels proved to be highly adaptable to different applications. The as-formed composites allowed for efficient dye removal with an adsorption capacity of 111.9 +/- 4 mg g(-1) in the case of methylene blue (MB). Integration of poly(ethyleneimine) (PEI) allowed for the selective capturing of Cr6+ ions with an adsorption capacity of 313 12 mg g-1. Most importantly, independent of the application, the magnetic rGO-loaded hydrogel can be regenerated without loss of its adsorption capacity. (C) 2017 Elsevier Inc. All rights reserved.